2017
DOI: 10.1210/jc.2017-00033
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor Bioactivity, Stanniocalcin-2, Pregnancy-Associated Plasma Protein-A, and IGF-Binding Protein-4 in Pleural Fluid and Serum From Patients With Pulmonary Disease

Abstract: Pathological pleural fluid is characterized by increased in vitro IGF bioactivity and elevated concentrations of PAPP-A, an IGF-activating proteinase. Thus, the tissue activity of the IGF system may differ substantially from that of the circulating IGF system. The correlation between IL-6 and PAPP-A indicates that inflammation plays a role in promoting local tissue IGF activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…In 2013, a whole-exome sequencing study of lung adenocarcinoma patients identified PAPPA2 gene mutations that were associated with prolonged survival times ( 40 ). In 2017, the present authors investigated PAPP-A, PAPP-A2 and IGF activity in pleural fluid collected at baseline from a limited number of patients with lung cancer ( n = 24) ( 18 ). The study showed that the distribution of IGF system proteins in pleural effusions was substantially different from that of the circulating IGF system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, a whole-exome sequencing study of lung adenocarcinoma patients identified PAPPA2 gene mutations that were associated with prolonged survival times ( 40 ). In 2017, the present authors investigated PAPP-A, PAPP-A2 and IGF activity in pleural fluid collected at baseline from a limited number of patients with lung cancer ( n = 24) ( 18 ). The study showed that the distribution of IGF system proteins in pleural effusions was substantially different from that of the circulating IGF system.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, PAPP-A causes a release of bioactive IGF in close proximity to the IGF-IR. Shifts in PAPP-A levels have been suggested to modify the relationship between bound and free IGF in various neoplasms ( 8 , 18 20 ). In patients with lung cancer, serum PAPP-A levels have been shown to be elevated ( 19 ), and down-regulation of PAPP-A expression decreases lung cancer progression in vivo ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we have recent data indicating that PAPP‐A only affects IGFBP‐2 marginally. In pleural effusions, where PAPP‐A is close to 50‐fold elevated as compared to serum, the degradation of IGFBP‐2 remains similar to that in serum and in serum from lung cancer patients the major part of IGFBP‐2 circulates in its free form (data in preparation). On the basis of our recent and present data, we speculate that in vivo, IGFBP‐2 is primarily unoccupied and hence not only protected against PAPP‐A degradation but also able to suppress PTEN .…”
Section: Discussionmentioning
confidence: 94%
“…The KIRA assay was used to assess residual ligand bioactivity in the circulation of IGF-TRAP-treated mice and performed as described in detail elsewhere 19 , 29 including recent modifications 30 . In brief, HEK293 cells overexpressing IGF-1R were cultured in complete DMEM medium (containing 1% Penicillin/Streptomycin, 0.5 mg/ml G418, 0.25 mg/ml Hygromycin, 10% FCS).…”
Section: Methodsmentioning
confidence: 99%